浅析适用于本地中学生的修辞及修辞教学手法 = The introductory study of relevant Chinese rhetorical devices and its teaching methodology for secondary school students - 刘译瑞 Liu, Yirui (2009)
日常生活中，不论是口语还是书面语上的沟通，人们并没有察觉自己语言中经常运用修辞来修饰他们的语言。虽然修辞如此普遍，中学生对修辞的了解仍然颇陌生，而且对于它的运用方法也不熟悉。本文希望通过平凡化修辞，进而使修辞的使用率频繁化而提出一些针对中学生的修辞教学手法的浅见。本文将通过以下的步骤来达到以上的目的：• 从本地报章以及歌词中显示辞格使用的普遍性；• 进行一项问卷调查来了解学生们对修辞的理解程度；• 分析学生的作文以了解他们运用辞格的使用率；• 依据以上所总结出的结论而选择出适当并适合中学生程度的辞格；• 为选择出的三个辞格—譬喻、拟人及移就兼通感提供更简明的定义，并且也将相近的辞格分辨清楚；• 分析这三个辞格在中二高级华文及中二快捷华文课本中的使用情况以及修辞效果；• 提出如何平凡化辞格的形象，以及如何将其使用率更频繁化的修辞教学手法建议。因此，希望本文能将修辞的概念更加平凡化，减少它在人们心中的陌生感，并且能促进学生运用辞格的使用率更加频繁化。In daily life, everyone is constantly engaged in communication through verbal and written means, and their prolific use of rhetorical devices often goes unnoticed. Even though the use of rhetoric devices is so habitual, it seems that secondary school students are not familiar with it and its usage. This thesis aims to propose teaching methodology to increase the frequency of usage of selected rhetorical devices through its simplification, as much as with the agenda of promoting widespread usage of these devices in writing for secondary school students. It is hoped that through this thesis, the concept of rhetoric will be less foreign and the usage of rhetorical devices will become more widespread among secondary school students.